2012
DOI: 10.1007/s11434-012-5253-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped graphene nanosheets as high efficient catalysts for oxygen reduction reaction

Abstract: It is of great significance in exploring alternative catalysts to platinum (Pt)-based materials for oxygen reduction reaction (ORR), because this reaction is invariably involved in various fuel cells and metal-air batteries. We herein reported the nitrogen doped graphene nanosheets (NGNSs) with pore volume of as high as 3.42 m 3 /g and investigated their potential application as ORR catalysts, it was demonstrated the NGNSs featured high activity, improved kinetics and excellent long-term stability for ORR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Fig. 9 Cyclic voltammograms of nitrogen-doped graphene nanosheets annealed at 900 C (NGNSs-900), nitrogen-doped graphene nanosheets annealed at 750 C (NGNSs-750), commercial Pt/C (10 wt%), graphene and C 3 N 4 coated graphene performed in 0.1M KOH solution with potential range À0:8 to þ0:2 and scan rate 50 mV/s [83] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 9 Cyclic voltammograms of nitrogen-doped graphene nanosheets annealed at 900 C (NGNSs-900), nitrogen-doped graphene nanosheets annealed at 750 C (NGNSs-750), commercial Pt/C (10 wt%), graphene and C 3 N 4 coated graphene performed in 0.1M KOH solution with potential range À0:8 to þ0:2 and scan rate 50 mV/s [83] …”
Section: Resultsmentioning
confidence: 99%
“…8 A typical setup of MFC using a biocathode, where oxygen and chemical reactants are reduced. The system can be used to generate power or to drive biochemical synthesis reactions to synthesis valueadded chemicals available Pt (10 wt%) for ORR [81,83]. In another study, nitrogen-doped CNTs were found to have higher electrocatalytic activity, lower overpotential and long-term stability for ORR than commercially available Pt (20 wt%, E-TEK) [84].…”
Section: Cathode With Metal-free Catalystmentioning
confidence: 99%
“…Other type of fuel cells where metal-free N-modified catalysts have been used as cathodes are microbial fuel cells in neutral conditions resulting in better performance than with Pt [74,75] [76].…”
mentioning
confidence: 99%
“…Additionally, the maximal current density was 23.34 A m −3 for the NGNSs-based MFC (Fig. 4d), which was around 1.2 times higher than that achieved in Pt/C-MFC under identical conditions (19.3 A m −3 ) [14,52]. However, the conductivity of regular NG was measured to be 35 S m −1 , which was still 10 S m −1 lower than Pt/C [4,50].…”
Section: Metal Free Catalysts Cathode Catalystsmentioning
confidence: 81%
“…In addition to being an excellent catalyst support, the potential of using graphene-based cathode/anode electrode in MFCs has also been demonstrated in some studies [13][14][15][16][17][18][19]. All studies revealed the great potential of using graphene to improve the electrode performance in MFCs.…”
Section: Reviewmentioning
confidence: 95%